Consumer Perception Towards Eco-friendly FMCGs in Coimbatore City - Samsai, T.; Praveena, S.; Nivetha, T. (International Journal of Bio-resource and Stress Management, 2018)
The environmental issues such as global warming, ozone depletion, water and air pollution, loss of species, and farmland erosion have led to the current alarming environmental crisis that threaten the environment as well as human life. The corporate social responsibility is one of the main factors which may influence the market performance of the company business. Environmental issues are very common now a day that should be addressed by the companies through offers in terms of eco-friendly products. Nowadays, there is an increasing trend among the marketer and consumer to switchover eco-friendly products and many companies have accepted their responsibility not to harm the environment and not to waste the natural resources. They have been under pressure to communicate their sustainability performance to their stakeholders. Hence, the present study aims to know about how the consumers care for their health and also their interest in protecting the environment. Coimbatore city were purposively selected for the study. Totally 100 consumers were selected by proportionate random sampling method. Both primary and secondary data were collected and utilized for the study. From the results it was observed that most of them aware about the eco-friendly products through advertisements and they are purchasing the eco-friendly products for health conscious. Most of the respondents are purchasing Himalayas and Dabur brands for their quality through advertisement.